Impact of Water, Sanitation and Hygiene (WASH) Facilities on Patient Satisfaction in Government Hospitals: Evidence from India - Bathala, Venkatesh; Subbarayudu, Dr. Y. (International Journal of Aquatic Research and Environmental Studies, 2026)
Access to Water, Sanitation and Hygiene (WASH) services are essential for quality health services, patient safety and infection prevention. But there is scanty empirical evidence of the impact of WASH facilities on patient satisfaction in Indian Government Hospitals. The study analysed the effect of WASH facilities on the satisfaction of the patients in government hospitals in Andhra Pradesh, India. A cross-sectional survey was carried out of 300 in-patients with primary data gathered using a structured questionnaire of five dimensions of WASH FIT, namely: water, sanitation, healthcare waste management, hand hygiene, environmental cleaning. Descriptive statistical analysis, reliability analysis, pearson correlation and multiple linear regression were used to analyze the data in SPSS version 22. The reliability coefficients obtained were between 0.75 and 0.87 which means the internal consistency of the measurement scale was satisfactory. The results showed that water, sanitation, and healthcare waste management had significant and positive effects on patient satisfaction, while no statistically significant effects were found for hand hygiene and environmental cleaning. The study adds to the paucity of empirical research on WASH and patient satisfaction in government hospitals in India, and is the first to isolate the WASH aspects most important to the patient’s experience of the quality of health care. The results will be useful for hospital management and policy makers, who should focus on investing in water supply, sanitation, waste disposal in the health care system, as well as the comprehensive quality improvement initiatives to strengthen the patient centred health care delivery and nurturing sustainable health care systems.